Analisis Metakomunikasi Politik dalam Proyek Pemindahan Ibu Kota Negara (IKN) Nusantara - Sukma, Agus Hitopa; Soepriyadi, Irzan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The relocation of the State Capital (IKN) from Jakarta to Nusantara is one of the largest strategic projects initiated by the government. This policy is based on the excessive burden on Jakarta and the economic disparity between Java Island and other regions in Indonesia. The remarkably swift legislative process for the IKN Law has created a public perception that speed was prioritized over thorough deliberation, which has the potential to erode public trust. This study aims to reveal the political metacommunication behind the IKN relocation project. The analysis was conducted to uncover the hidden meanings, power dynamics, and underlying intentions behind political statements and actions related to IKN. This research uses a political metacommunications analysis approach, which serves to uncover the "message within the message" conveyed through verbal and non-verbal cues. The analysis was performed on the official government narrative, public counter-narratives and criticism, and the role of the media in the IKN metacommunication landscape. The findings indicate that the official government narrative attempts to frame IKN as a symbol of progress, equity, and unity, reinforced by the use of symbols like "Nusantara" and "Pohon Hayat". However, this narrative is confronted by a strong counter-narrative from civil society and academics who highlight the rushed legislative process, environmental impacts, and financial ambiguities. These implicit messages point to a "democratic deficit" and "financial vulnerability". The role of the media and social media dynamics also contributes to reinforcing these competing narratives. In conclusion, the legitimacy of the IKN project does not solely depend on the grand vision and physical development, but also on the complex interaction between explicit and implicit messages. The project's success will be determined by the government's ability to align its rhetoric with its actions, building genuine trust and accountability.
Keywords: Political Metacommunication; IKN Nusantara; Symbolic Communication; Legitimacy; Counter-Narrative